Business Migration to Ireland - Gusciute, Egle; Quinn, Emma; Barrett, Alan (ESRI, 2015)
This European Migration Network Study maps measures and policies that are in place to facilitate and encourage business migration from non-EEA countries to Ireland and examines to what extent the immigration system is ‘business friendly’.